Evaluating recreational resources of Southeast Johor using remotely sensed data. - Mansor, Shattri; Mansor, Mohd. Isa; Hassan, Azmi (1989)
Land evaluation for recreational land use is becoming more important in these days. Increasing numbers of people take part in recreational activities and the income from tourism is a welcome support to the economy of many countries including Malaysia. Therefore proper management of these resources is clearly needed. A study has been undertaken to evaluate natural resources for recreational land use utilizing SPOT1 MSS data and aerial photographs. Case study of Southern Johor is presented.